Permissions, a survival guide : blunt talk about art as intellectual property - Bielstein, Susan M. (Chicago guides to writing, editing, and publishing., 2006)
If a picture is worth a thousand words, then it's a good bet that at least half of those words relate to the picture's copyright status. Art historians, artists, and anyone who wants to use the images of others will find themselves awash in byzantine legal terms, constantly evolving copyright law, varying interpretations by museums and estates, and despair over the complexity of the whole situation. Here, on a white--not a high--horse, Susan Bielstein offers her decades of experience as an editor working with illustrated books. In doing so, she unsnarls the threads of permissions that have ensna.